Performances of facades of buildings in mitigating the urban heat island effect - Hj Mohd Ariffin, Noor Aziah; Phoo, Pwint Thu Aung (Zes Rokman Resources (2131022-P), 2018)
A building’s façade plays an important role in moderating the overall performance of buildings. Apart from its aesthetic and visual impacts, a façade influences the thermal performance within the building as well as its immediate environment. In achieving sustainable development and reducing the Urban Heat Island (UHI) effect, efficient façade systems and products must be appropriate to the climatic characteristics. UHI is the effect of the increment of anthropogenic ambient temperatures in urban areas as compared to the rural areas. Buildings and urban development in cities are the causal links of UHI leading to greater use of energy consumption. In Malaysia, temperatures in cities are 6 – 7 degrees higher and the Green Building Index (GBI) (amongst other energy ratings) is taking that responsibility to ensure that not only energy but also thermal performances of buildings are optimized. One of the criteria in GBI to increase a building’s overall performance lies in the ability of facades to moderate and augment a building’s internal and external temperatures. This study considered the impact of the facades of buildings on the thermal performances of outdoor environments immediate to buildings in an urban setting in mitigating urban temperatures. Several building facades from both GBI and non-GBI rated buildings in Klang Valley were the test cases in this investigation. The GBI certified buildings tested used curtain-walling or glass facades (GF). The non-GBI buildings tested used double skin façade (DSF) and other skin (opaque) facades. Data monitoring was conducted, and results showed that temperatures surrounding the DSF were lower than the GF prompting need of better facade designs in mitigating the Urban Heat Island effect for the tropical climate. The significance of this paper is as a guideline to building designers and authorities in making decisions for achieving overall efficiency in new buildings and even for existing ones. The design considerations for the façades of buildings are crucial in aiding to mitigate the UHI effects.